CO2 assisted deposition of R/S-ibuprofen on different porous carrier materials: Influence of carrier properties on loading and dissolution behavior. (May 2018) - Reiser, Sarah; Shaban, Masoom; Weber, Alfred; Türk, Michael
Graphical abstract: Highlights: Ibuprofen loaded carriers were successfully prepared in scCO2 . Carrier properties influences the loading capacity and dissolution behavior. Dissolution rate depends on drug crystallinity and pH-value of the aqueous media. Using scCO2 technology and conditions, efficient drug / carrier systems were produced. Abstract: With regard to bioavailability of poorly water-soluble drugs a big goal in research is to improve their dissolution behavior in the gastrointestinal tract. One suitable way to enhance the bioavailability is the use of drug loaded carrier materials. However, the effect of carrier properties such as specific surface area, pore size and pore volume on the dissolution of drugs is not well known yet. To investigate this, carrier materials with defined properties were produced by Salt Assisted Spray Pyrolysis (SASP) and loaded with racemic ibuprofen by the Controlled Particle Deposition (CPD) process. Their loadings and dissolution rates were compared to those of MCM-41 and SBA-15. It was found that the ibuprofen loading on the SASP carrier materials is lower due to their smaller specific surface areas, whereas their dissolution rates were higher in comparison to CPD processed MCM-41 and SBA-15. Furthermore, it was observed that pore size and pore volume influence the loading capacity of carrier materials. Wider mesopores lead to multilayer formation where crystalline ibuprofen structures were detected by XRD analysis. N2 -adsorption/desorption experiments at T = 77 K on the CPD processed carriers lead to the assumption that the small mesopores of MCM-41 or SBA-15 were occupied by ibuprofen due to the shift of the typical capillary condensation step at p/p0 = 0.3–0.4 (untreated material) towards lower relative pressures of the CPD processed carriers.